THE INDONESIAN SUPREME COURT REGULATION: ENABLING OFFENDERS AND VICTIMS TO FULFILL RESTORATIVE JUSTICE AGREEMENTS DURING PROBATION - Alya Dean Putri; Prija Djatmika; Setiawan Nerdajasakti (CV. RADJA PUBLIKA, 2025)
This study investigates the application of conditional sentencing within the framework of restorative justice as outlined in Indonesian Supreme Court Regulation (PERMA) No. 1 of 2024. This regulation offers a mechanism that enables offenders to fulfill their obligations from restorative agreements during the probation period, promoting both offender accountability and victim restoration. The research analyzes the procedural aspects of restorative justice in criminal cases in Indonesia, particularly focusing on how it is implemented in courts. It highlights the benefits of integrating restorative justice with conditional sentencing, while also identifying challenges and gaps in the legal framework. Additionally, the study calls for further empirical research to evaluate the practical effectiveness of this approach and the legal consequences if offenders fail to fulfill their obligations during the probation period.